Re-Thinking a Structural Model for M-Phone Paying among South African Consumers - N., Dlodlo (Journal of Economics and Behavioral Studies, 2017)
Contemporary payment systems have transformed global businesses extensively. Nevertheless, despite its vast prospects, the widespread utilisation of mobile phone technology for payment transactions (m-phone paying) and reproduction of pecuniary structures has only been hemmed in among a small number of markets. The proliferated reliance on mobile payment services has not been witnessed universally, suggesting that even success stories are still ambivalent and as a result, cannot be easily replicated. This paper is intended to address this issue by evaluating the determining factors towards the continued use of m-phone payment services by existing South African customers. The research model was tested using SMART PLS 3, upon examining the antecedents of users’ intentions toward embracing the emerging mobile phone in commercial transactions. A cross-sectional study was performed on a sample of 474 consumers, wherein security and usefulness were validated as having significant and direct effects on consumers’ attitude towards m-phone paying, of which the latter influences future intentions. The relevance of customers’ future intentions towards m-phone paying was established, thereby sanctioning the idea to include the variable as a proxy for actual usage in technology adoption research. This study provides sound reason for cumulative research that seeks to refine novel models of technology acceptance even further. For marketers and m-phone technologists, understanding the key determinants is vital towards the upgrade and implementation of m-phone payment services. In lieu of this, delivering m-phone applications and payment services that achieve high usage, value and consumer laudation will be an inevitable boon.